Socio-Psychological Drives and Mechanisms of Individual Behavior in Society - Bochelyuk, Vitaliy (Psychological Prospects Journal, 2017)
The article deals with the social psychological motives and mechanisms of human behavior in society. The emphasis is that a personal existence appears as internal necessity and need, objectively expands the defined time limits, revealing the behavioral orientation of a personality, appealing to his main reason, which stands as a basis of a personality. The basis is embodied in a particular life position which allows a person to solve the problem of devoting himself and his own life, the actions which should be done every single moment. The life of a person is different if he really knows what is most important for him and manages meaningful things according to it. Realizing once his vital credo, a person finds the basis for his life activity. Particular attention is paid to the systematization of various factors predicting personal behavior. They have different meanings in predicting the future actions of the individual. Motives and mechanisms of human life are interpreted as those that ensure the production and reproduction of the total life resourse of a person. It is assumed that a person «does not know» his total vital resource, he cannot always appreciate it, but he has some idea of it; and it is the very basis that determines the nature and level of claims. In addition it precisely forms and directs a certain way of social behavior oriented toward social objects and relationships (and not to psychological states), that changes a person into a member of society, and not just an isolated author of his own «Self».